(untitled) (World Bulletin of Public Health, 2024)
According to mass surveys of urban and rural populations, hearing organ pathology is observed in 6% of residents; approximately 0.65— 2% of them have a pronounced hearing impairment, which makes speech communication difficult. Clinical observations indicate that among surdological patients there are persons with mixed cochleo-vestibular lesions, diseases of the vestibular apparatus, in which there is a need to study not only auditory, but also vestibular functions to establish the nature of the lesion and the choice of treatment tactics